"All My Problems Go Away for 90 Minutes": How Football and Psychotherapy Improves Young Men's Mental Health. Issue 5 (October 2020) - McGrane, Amy; Bird, Niamh; Arten, Chelsea; O'Sullivan, Katriona
This qualitative research sought to establish the impact of an 8-week program combining football and one-to-one psychotherapy on young males' mental health, determining the factors that predict help-seeking behaviors in this group of men. Pre- and post-participation focus groups were used as the method of data collection. Six males (19–35 years old; M = 25.5) completed both pre-intervention and follow-up focus groups. Help-seeking behaviors were influenced by the appeal of football and the perception of the counselor being accessible. Barriers included gender norms, socialization, financial difficulties, and challenging social landscapes. Post-participation focus groups revealed that positive social and counseling relationships facilitated improved mental health. Sport was deemed an acceptable medium to deliver a mental health intervention as it increased social connections and facilitated help-seeking. Findings support previous research indicating that combining sports and psychotherapy positively impacts young males' mental health.